Neuro-developmental Disorders with Co-Morbid Affective Disorders Sometimes Produce Psychiatric Conditions Traditionally Diagnosed as Schizophrenia - FITZGERALD, MICHAEL (My University, 2013)
The knowledge in psychiatric genetics, neuroanatomy, functional neuroanatomy, neuropsychology, neuropsychopharmacology and clinical psychiatry, has immensely increased in the last decades. h ere, the psychiatric conditions schizophrenia, affective disorders and autism spectrum disorder are discussed. Reported findings in relevant literature and our clinical experience in adult psychiatry in line with these findings, are subjects of this article. d isorders that in the last 100 years typically have been described as schizophrenia might today be better viewed as neurodevelopmental disorders (N dd :s), particularly autism spectrum disorder, combined with affective disorders. a lso in affective disorders, without any signs and symptoms typical of a diagnosis of schizophrenia, N dd :s are very common, albeit generally less severe. t he ensuing view on schizophrenia and on affective disorders respectively has very important and far reaching conceptual and clinical implications
PUBLISHED
Keywords: Neuroscience; (SCHIZOPHRENIA); ADULT SCHIZOPHRENIA; Adolescent Psychiatry; CHILD PSYCHIATRY; COMMUNITY PSYCHIATRY; CONSULTATION LIAISON PSYCHIATRY; CONSULTATION-LIAISON PSYCHIATRY; GENERAL HOSPITAL PSYCHIATRY; LIAISON PSYCHIATRY; Neurodevelopmental Disorders; Neuropsychiatry; Neuropsychiatry; PSYCHIATRY; Philosophy of Psychiatry; Psychiatry; Psychiatry; SCHIZOPHRENIA FAMILIES; Schizophrenia; Schizophrenia; Schizophrenia; TRAINEES IN PSYCHIATRY; child and adolescent Psychiatry; forensic psychiatry; neurodevelopmental psychiatry; psychiatry services